Innate immune cell activation after HIV-1 vaccine administration is associated with increased antibody production - N’guessan, Kombo F.; Machmach, Kawthar; Swafford, Isabella; Costanzo, Margaret C.; Wieczorek, Lindsay; Kim, Dohoon; Akapirat, Siriwat; Polonis, Victoria R.; Pitisuttithum, Punnee; Nitayaphan, Sorachai; Gurunathan, Sanjay; Sinangil, Faruk; et al. (Frontiers in Immunology, 2024)
The RV144 Thai phase III clinical trial’s canarypox–protein HIV vaccine regimen showed modest efficacy in reducing infection. We therefore sought to determine the effects of vaccine administration on innate cell activation and subsequent associations with vaccine-induced immune responses. RV306 was a randomized, double-blind clinical trial in HIV-uninfected Thai adults that tested delayed boosting following the RV144 regimen. PBMC collected from RV306 participants prior to and 3 days after the last boost were used to investigate innate immune cell activation. Our analysis showed an increase in CD38+ mucosal associated invariant T (MAIT) cells, CD38+ invariant natural killer T (iNKT) cells, CD38+ γδ T cells, CD38+, CD69+ and HLA-DR+ NK cells 3 days after vaccine administration. An increase in CD14-CD16+ non-classical monocytes and CD14+CD16+ intermediate monocytes accompanied by a decrease in CD14+CD16- classical monocytes was also associated with vaccine administration. Inclusion of ALVAC-HIV in the boost did not further increase MAIT, iNKT, γδ T, and NK cell activation or increase the proportion of non-classical monocytes. Additionally, NK cell activation 3 days after vaccination was positively associated with antibody titers of HIV Env-specific total IgG and IgG1. Vδ1 T cell activation 3 days after vaccine administration was associated with HIV Env-specific IgG3 titers. Finally, we observed trending associations between MAIT cell activation and Env-specific IgG3 titers and between NK cell activation and TH023 pseudovirus neutralization titers. Our study identifies a potential role for innate cells, specifically NK, MAIT, and γδ T cells, in promoting antibody responses following HIV-1 vaccine administration.